1991
DOI: 10.2337/diab.40.4.462
|View full text |Cite
|
Sign up to set email alerts
|

Vanadate Induction of L-type Pyruvate Kinase mRNA in Adult Rat Hepatocytes in Primary Culture

Abstract: In primary culture of adult rat hepatocytes, vanadate in the presence of glucose stimulates the expression of the liver (L-type) pyruvate kinase gene. Glucose by itself was inactive, and vanadate, like insulin, was also inefficient in the absence of glucose. Similar results were obtained on glucokinase gene expression. An analogue of cAMP, 8-(4-chlorophenylthio)-cAMP, inhibited the production of L-type pyruvate kinase and glucokinase mRNAs in the presence of glucose plus vanadate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 21 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…In the liver of STZ‐induced diabetic rats, the levels of Fru‐2,6‐P 2 and 6‐phosphofructo‐2‐kinase activity decreased and the phosphorylation of the bifunctional enzyme increased, correlating with a fall in hepatic Fru‐2,6‐P 2 , ketonaemia and glycaemia [24–26]. Similar results have been reported in diabetic mouse liver, underscoring the role played by Fru‐2,6‐P 2 in the control of fuel metabolism [27].…”
Section: Introductionsupporting
confidence: 53%
“…In the liver of STZ‐induced diabetic rats, the levels of Fru‐2,6‐P 2 and 6‐phosphofructo‐2‐kinase activity decreased and the phosphorylation of the bifunctional enzyme increased, correlating with a fall in hepatic Fru‐2,6‐P 2 , ketonaemia and glycaemia [24–26]. Similar results have been reported in diabetic mouse liver, underscoring the role played by Fru‐2,6‐P 2 in the control of fuel metabolism [27].…”
Section: Introductionsupporting
confidence: 53%
“…The corrective action of vanadium salts was attributed to the enhancement of glucose oxidation and metabolism through activation and/or induction of the reduced hepatic glycolytic enzymes together with suppression of the overexpressed gluconeogenic enzymes, especially phosphoenolpyruvate carboxykinase (PEPCK)18, 37–42. The activity and gene expression of a large group of insulin dependent enzymes was enhanced, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, L-PK mRNA concentration decreases in diabetes, and increases following insulin administration [32,33]. Moreover, vanadate can mimic insulin by increasing L-PK mRNA in cultured hepatocytes [15]. As expected, L-PK mRNA level was reduced to 15 % of the control value in the liver of diabetic rats.…”
Section: Resultsmentioning
confidence: 66%
“…Noguchi et al [33] have suggested that insulin may increase transcription of the L-PK gene by stimulating the synthesis of some unknown protein. Recently, Miralpeix et al [15] have shown that vanadate mimics insulin action on L-PK and glucokinase transcription and, similar to insulin [34], vanadate cannot increase the L-type PK m R N A content in the absence of glucose. This indicates that neither vanadate nor insulin has a direct role on transcription of the L-type P K gene by itself, since glucose is required for its mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation